(untitled) (The International Journal for Scientific Research, 2026)
This study aims to analyze the environmental and hydrological characteristics of the city of Sager in the Riyadh Region and to detect the spatial changes it has undergone over the past twenty‑five years through the integration of spatial analysis techniques, remote sensing, and geographic information systems (GIS). The research relies on combining Digital Elevation Model (DEM) data with a 10‑meter resolution, multi‑temporal satellite imagery (Landsat 2000-2008–2025 and Sentinel‑2-2018), climatic records from King Khalid Airport meteorological station, structural planning maps, and field verification, in order to construct an integrated spatial database that supports the interpretation of surface dynamics, wadi networks, and patterns of urban expansion. The topographic analysis reveals that the surface of Sager gradually descends from east to west, with elevations ranging between 700 and 747 meters above sea level, and is dominated by gentle slopes that direct surface runoff toward Wadi Alqarnah in the east and Wadi Sager in the west. The study also shows that urban expansion between 2000 and 2025 followed a guided pattern influenced by surface characteristics and the presence of wadis, as the built‑up area increased from 4.153 km² to approximately 9.871 km², with significant expansion toward the north and northwest, accompanied by a noticeable decline in agricultural lands in the northern and eastern outskirts. The study employed the Index‑Based Built‑up Index (IBI) as a composite spectral indicator capable of distinguishing built‑up areas from vegetation and water bodies, enabling more accurate detection of urban growth and identification of encroachments on wadi channels. Spatial analysis using a 100‑meter buffer around wadi courses revealed that large areas of buildings lie within natural flow paths, with encroachments on Wadi Alqarnah reaching 441,562.66 m² and those on Wadi Sager reaching 952,098.93 m²areas highly susceptible to inundation during flood events. The study further highlights the region’s sensitivity to extreme rainfall events. The 2008 incidentduring which rainfall exceeded 90 mm within a few hours—demonstrated that the wadis still retain their natural role in conveying surface runoff, and that unregulated urban expansion into floodplains has contributed to the inundation of several neighborhoods and farms, particularly in the western and southwestern parts of the city. The study concludes that understanding the topographic and hydrological characteristics of Sager, and linking them to patterns of urban expansion, is essential for effective flood‑risk management. It emphasizes the need to guide future urban growth away from wadi corridors, enhance environmental awareness, preserve natural vegetation cover, and update urban planning frameworks in accordance with the geomorphological nature of the floodplain and historical flow paths.